2016
DOI: 10.1016/j.mayocp.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

To Screen or Not to Screen

Abstract: Screening is the early detection of a latent disorder by a test to allow early intervention with the aim of improving prognosis. Individual and population perspectives on screening are perceived as opposing interests of patients and the population. In this article, we try to reconcile these perspectives. The individual perspective is based on the clinical experience of a better prognosis at early stages and patients with missed opportunities. In the population perspective, screening is based on a population-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Some authors have discussed perceived challenges of autonomous decision-making within the context of a population-based cancer screening program (Elston Lafata et al, 2017; Jepson et al, 2005; Salmi et al, 2016; van Dam, Kuipers, Steyerberg, van Leerdam, & de Beaufort, 2013). In the cervical screening situation, many HCPs were concerned about offering modalities to patients that were considered inferior to the modalities recommended by clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have discussed perceived challenges of autonomous decision-making within the context of a population-based cancer screening program (Elston Lafata et al, 2017; Jepson et al, 2005; Salmi et al, 2016; van Dam, Kuipers, Steyerberg, van Leerdam, & de Beaufort, 2013). In the cervical screening situation, many HCPs were concerned about offering modalities to patients that were considered inferior to the modalities recommended by clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study demonstrated an interesting paradox that HCPs and individuals trusted cancer agencies and networks to know the “best” options for cervical screening for individuals, yet, some respondents also expected system-level institutions to prioritize financial or other system prerogatives above an individual’s wellbeing. As test acceptability is a crucial component of a successful screening program (Dobrow, Hagens, Chafe, Sullivan, & Rabeneck, 2018; Salmi et al, 2016; Wilson & Jungner, 1968), women want confirmation from HCP stakeholders that the options are valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with canonical screening practices [ 35 , 114 , 115 ], most panelists agreed that screening should only be carried out where post-screening follow-up is available. They considered it would be unethical to burden C&A and their families with positive screening results in the absence of access to effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some experts are wary of applying population preferences in individual encounters for cancer screening because extrapolating might be inaccurate or ignore individual's autonomy in decision-making. 10,55,56 Many researchers are currently investigating robust methods to elicit and synthesize preferences for use in population-level recommendations. 14,15,57,58 "Cervical cancer screening-it's your choice" was designed to inform future person-centred cervical cancer screening guidelines and met the quality criteria of an individual-level decision tool.…”
Section: Discussionmentioning
confidence: 99%